Salvia miltiorrhiza (Danshen) promotes Achilles tendon repair: from network pharmacology prediction to in vivo mechanistic validation - Wang, Yu; Xie, Xianyan; Yang, Gaoyuan; Li, Ziyan; Qin, Shuqi; Luo, Junze; Jia, Xiaoxu; Li, Yifeng; Zhu, Lin; Wang, Huiguo (Frontiers in Pharmacology, 2025)
ObjectiveTo investigate the key bioactive component of Salvia miltiorrhiza (Danshen) for repairing Achilles tendon injury and to elucidate its underlying mechanisms.MethodsA network pharmacology approach was employed to screen for common targets for Danshen in Achilles tendon repair, identifying Tanshinone IIA (Tan IIA) as the key bioactive component. Its targets were then subjected to Protein-Protein Interaction (PPI) and KEGG pathway analyses. Subsequently, a rat model of Achilles tendon injury was established. After a 4-week intervention with Tan IIA, its reparative effects were comprehensively evaluated using histological, biomechanical, immunohistochemical (IHC), and ELISA methods.ResultsNetwork pharmacology predicted that Tan IIA acts through core targets such as AKT1 and EGFR to regulate pathways including PI3K-Akt and MAPK. In vivo experiments confirmed that, compared to the model group, Tan IIA significantly improved tissue structure (histological score, P < 0.001) and enhanced the ultimate tensile load (P < 0.01). It also upregulated Collagen Type I (COLⅠ) expression (P < 0.05) while downregulating Vascular Endothelial Growth Factor A (VEGFA) expression (P < 0.01), and effectively modulated serum inflammation by decreasing IL-6 (P < 0.01) while increasing IL-10 and TGF-β (P < 0.05).ConclusionTan IIA is the key bioactive component of Salvia miltiorrhiza for repairing Achilles tendon injury. It effectively promotes the structural and functional healing of the tendon by synergistically regulating key processes such as inflammation, matrix remodeling, and angiogenesis.